Exploring Stress Levels, Job Satisfaction, and Quality of Life in a Sample of Police Officers in Greece - Evangelos C. Alexopoulos; Vassiliki Palatsidi; Xanthi Tigani; Christina Darviri (Elsevier, 2014)
Background: The ongoing economic crisis in Greece has affected both stress and quality of life (QoL) at all socioeconomic levels, including professionals in the police force. The aim of this study was to examine perceived stress, job satisfaction, QoL, and their relationships in a sample of police officers in Greece. Methods: A cross-sectional study was conducted during the first trimester of 2011 in 23 police stations in the greater Athens area. A total of 201 police officers agreed to participate (response rate 44.6%). The General Health Questionnaire-28 (GHQ-28) was used to assess general health, and the World Health Organization Quality of Life-BREF Questionnaire and Perceived Stress Scale-14 (PSS-14) questionnaires were used to assess QoL and perceived stress, respectively. Results: The PSS and GHQ subscales and total scores exhibited strong, positive, and significant correlations coefficients (r): 0.52 for somatic disturbances, 0.56 for stress and insomnia, 0.40 for social dysfunction, and 0.37 for depression, yielding an r equal to 0.57 for the total GHQ score. A higher level of perceived stress was related to a lower likelihood of being satisfied with their job; in this regard, male participants and higher ranked officers reported lower job satisfaction. The PSS and GHQ scores were inversely, consistently, and significantly related to almost all of the QoL aspects, explaining up to 34% of their variability. Parenthood had a positive effect on QoL related to physical health, and women reported lower QoL related to psychological health. Conclusion: Higher levels of stress are related to an increased risk of reporting suboptimal job satisfaction and QoL. The magnitude of these associations varied depending on age, gender, and rank, highlighting the need for stress-management training.